Thermal-sprayed dielectric coating e.m. properties evaluation via free-space measurements at microwave frequencies. (21st November 2008) - Nanni, F.; Cipri, F.; Casadei, F.; Valente, T.
At present, there is a lack of knowledge about the electromagnetic (e.m.) properties of alumina coatings in a wide microwave frequency range. In this paper, complex permittivity of thermal sprayed alumina coatings were evaluated via free-space measurements. XRD, microstructural and microhardness characterisations were performed too. The results showed that the real part of permittivity is consistent with that found for bulk alumina, being the difference due to the complexity of the coating, which is composed by multiple phases originated during the deposition process. The bond coat measurements showed that it is possible to recognise an anisotropic texture of the coating.